Screening Flavonoids Compounds for Dipeptidyl Peptidase IV Inhibitory Activity by Using Molecular Docking Method - Thanh Tung, Bui; Thanh Chuc, Nguyen; Thi Ngoc, Le; Thi Hoai Thanh, Vo (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 40 No 3, 2024)
Diabetes mellitus causes hyperglycemia and disrupts metabolic processes in the body. The enzyme dipeptidyl peptidase IV (DPP-IV) plays a crucial role in regulating blood glucose levels by modulating the activity of glucagon-like peptide-1 (GLP-1). Inhibiting DPP-IV activity increases GLP-1 activity, which enhances insulin sensitivity and ultimately reduces blood glucose levels in patients with type 2 diabetes. Flavonoid compounds have been shown to have therapeutic effects in diabetes management. Therefore, this study aims to evaluate and screen flavonoid compounds for their DPP-IV inhibitory effects using molecular docking methods. Through docking results, drug-likeness assessment according to Lipinski's Rule of Five, ADMET pharmacokinetic and toxicity analysis, and target-compound interaction analysis, silibinin was identified as the most promising flavonoid among those screened. Further in vitro and in vivo studies should be conducted to assess the potential of this compound in supporting diabetes treatment.